Business Growth through Consumer Insights: The Economic Influence of Taste, Product Excellence, and Price - Haikal, Fikri; Ambarwati, Rita; Adji, Kumara (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze the influence of taste, product excellence, and cost impact or price on purchasing decisions for Sempol Gendut.Located on JL DR Wahidin GG 4 RT 011 RW 002 Bulusidokare Village, Sidoarjo District, Sidoarjo Regency, East Java, 61216. The data collection method uses a questionnaire and observation. The sampling method employed is simple random sampling, and the data analysis is conducted using the SEM PLS approach.Data processing in this study was carried out using Smart PLS version 4.0. Hypothesis testing was conducted through path direct effect tests and indirect effect tests. The analysis results revealed that the taste variable has a positive and significant influence on purchasing decisions, while the product excellence and cost variables also demonstrated positive and significant effects.